Socio-demographic differences in the frequent use of emergency department care by older persons: a population-based study in Stockholm County - Megan Doheny; Janne Agerholm; Nicola Orsini; Pär Schön; Bo Burström (BMC, 2019)
Abstract Background In Sweden, the number of older people using emergency department (ED) care is rising. Among older persons an ED visit is a stressful event, which potentially could have been prevented or treated at other levels of care. Frequent ED use (> 4 visits a year) by older persons might reflect issues in the organisation of health care system to address their needs. We aimed to explore socio-demographic differences among older people seeking ED care in terms age and gender, and to investigate the association between income and frequent ED use. Methods A population-based study analysing the utilisation of ED care by (N = 356,375) individuals aged 65+ years. We linked register data on socio-demographic characteristics from 2013 to health care utilisation data in 2014. Multivariable logistic regression was used to estimate the income differences in the frequent use of ED care, adjusting for living situation, country of birth, residential area, age in years, multi-morbidity and the use of other health care services. Results Those 65+ years accounted for (27%) of all ED visits in Stockholm County in 2014. In the study population (2.5%) were identified as frequent ED users, who were predominantly in the lower income groups, living alone or in an institution, had more multi-morbidity, and utilised more of other health care services. The lowest income groups had a three-fold greater odds of being a frequent ED user than those in the highest income group. In the adjusted models, the odds were reduced by 12-44% for those in the lowest income groups. However, age and gender differences were observed with men 65-79 years (OR 1.75 CI: 1.51-2.03) and women 80+ years (OR 1.50, CI 1.19-1.87) in the lowest income groups having a higher odds of frequent ED use. Conclusion This study observed that ED visits by older persons are driven by a need of care, and those that frequently visit hospital-based EDs are a socially disadvantaged group, which suggests that the organisation of care for older people should be reviewed in order to better meet their needs in other levels of care.